Developing embodied cognition: insights from children’s concepts and language processing - Wellsby, Michele (Frontiers Media S.A., 2014)
Over the past decade, theories of embodied cognition have become increasingly influential with research demonstrating that sensorimotor experiences are involved in cognitive processing; however, this embodied research has primarily focused on adult cognition. The notion that sensorimotor experience is important for acquiring conceptual knowledge is not a novel concept for developmental researchers, and yet theories of embodied cognition often do not fully integrate developmental findings. We propose that in order for an embodied cognition perspective to be refined and advanced as a lifelong theory of cognition, it is important to consider what can be learned from research with children. In this paper, we focus on development of concepts and language processing, and examine the importance of children's embodied experiences for these aspects of cognition in particular. Following this review, we outline what we see as important developmental issues that need to be addressed in order to determine the extent to which language and conceptual knowledge are embodied and to refine theories of embodied cognition.